MULTIFOCAL ATHEROSCLEROSIS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND ITS COMBINATION WITH METABOLIC SYNDROME - Rzayeva, R.A. (World of Medicine and Biology, 2022)
The purpose of the study was to assess of the frequency of multifocal atherosclerosis and plural atherosclerotic plaques in the different vessels of patients with type 2 diabetes mellitus and its combination with metabolic syndrome. Results showed that 12.02 % of patients with diabetes mellitus without metabolic syndrome had multifocal atherosclerosis with simultaneous damage of 2 vessels, in patients with diabetes mellitus+metabolic syndrome – 22.75 % (p